TEACHING INFANTS AND TODDLERS IN TASKA BRIDGING DEVELOPMENTAL NEEDS AND PARENTAL EXPECTATIONS - Nurul Najwa Mahadi; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study explores the teaching and learning approaches implemented in Childcare Centres (TASKA) for infants and toddlers, focusing on how these methods address the aspirations of modern parents. The objective is to investigate how a TASKA teacher plans and applies age-appropriate teaching strategies that meet both children’s developmental needs and parental expectations. A qualitative approach was employed through a semi-structured interview with one experienced TASKA teacher. The findings provide insights into practical teaching methods, parental involvement, and challenges faced in aligning educational practices with contemporary parental aspirations. This study highlights the critical role of TASKA in fostering a supportive and effective early learning environment for young children.